A Semantic Analysis of Sentence, Utterance, and Pressuposition in the Short Story "The Black Cat" by Edgar Allan Poe - Apriliani Hafifah; Ghaida Muthmainah; Najwa Ferizka Setiawan; Ratu Hana Maulida (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
meaning in Edgar Allan Poe’s short story The Black Cat. Using a qualitative descriptive method, the research analyzed how language in the narrative especially through the narrator's expressions reveals deeper psychological and thematic meanings. Sentences in the story often carry layered meanings that go beyond literal interpretation, while utterances reflect the narrator’s unstable mental state and emotional contradictions. The study also identifies various presuppositions embedded in the text, which help uncover the narrator's assumptions and hidden guilt. The findings showed that Poe’s use of language invited readers to question the reliability of the narrator, and that semantic analysis enhances our understanding of the story’s dark, psychological depth. This research demonstrated that applying semantic theory to literary texts provided insight into character construction, narrative tension, and implied meaning